Hacia una nueva forma de comprensión de lo jurídico (2007)
Modern legal thought has tried to approach the study of juridical matters with an exclusively theoretical view; that is, attempting to make a description of the legal phenomenon while devising a system as appropriate as possible to explain that phenomenon, just as natural sciences choose a sector of reality to describe it by preparing a model serving to through light on them as best as possible. This manner of approaching things of juridical nature originates in the influence of modern rationalist philosophy, the boom experienced by the physical sciences since Newton’s Prinicipia mathematica, and the will to assimilate every science to the sciences of nature that, according to the modern thinkers, gave the best and most effective results. The consequence of this phenomenon was denial of the complexity of reality. The distinction between theoretical reason and practical reason loses all its sense, and law loses its nature as a practical and prudential science. This is why recovering the prudential level of legal science is necessary for it to respond more properly to the nature of its object: if juridical reality is a practical one in search of the resolution of specific cases, a method has to be found, to fit in with this object’s nature of the object, instead of insisting in adapting the method of theoretical sciences to the juridical object.